2015
DOI: 10.1016/j.jgr.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanism of Korean Red Ginseng on GM-CSF expression in UVB-irradiated keratinocytes

Abstract: BackgroundUV-irradiated keratinocytes secrete various proinflammatory cytokines. UV-induced skin damage is mediated by growth factors and proinflammatory cytokines such as granulocyte macrophage colony stimulating factor (GM-CSF). In a previous study, we found that the saponin of Korean Red Ginseng (SKRG) decreased the expression of GM-CSF in UVB-irradiated SP-1 keratinocytes. In this study, we attempted to find the inhibitory mechanism of SKRG on UVB-induced GM-CSF expression in SP-1 keratinocytes.MethodsWe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…There was no noted cytotoxic effect of red ginseng extract on the keratinocyte cells. These results support the antitumor, antimetastatic, and antiangiogenic properties of ginsenosides . It was also found that combining ginseng extract with Trichosanthis kirilowii (another herb used in traditional Asian medicine) inhibits melanogenesis in melanoma cells lines by decreasing tyrosinase activity and thereby decreasing melanin content in cells …”
Section: Plant‐based Additivessupporting
confidence: 61%
“…There was no noted cytotoxic effect of red ginseng extract on the keratinocyte cells. These results support the antitumor, antimetastatic, and antiangiogenic properties of ginsenosides . It was also found that combining ginseng extract with Trichosanthis kirilowii (another herb used in traditional Asian medicine) inhibits melanogenesis in melanoma cells lines by decreasing tyrosinase activity and thereby decreasing melanin content in cells …”
Section: Plant‐based Additivessupporting
confidence: 61%
“…In fact, numerous cosmetic products contain fractions previously prepared in Korea from P. ginseng (e.g., BG11001, P. ginseng berry, and AP-SF) [48] , [49] , [50] . Studies on individual compounds from P. ginseng have indicated that ginsenosides (G)-Rg2, G-F2, G-Re, and G-Rb2 protect skin and possess additional cosmeceutical activities by suppressing melanin biosynthesis, enhancing cyclic growth of hair follicles, improving skin barrier function, and suppressing skin inflammation [51] , [52] , [53] . Therefore, ginsenosides in BIOGF1K could contribute to its antiphotoaging activity, thereby increasing the value of this fraction as a cosmeceutical biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte derived paracrine factors stimulate melanocyte proliferation, leading to skin hyperpigmentation [18] . In a previous study, we found that SKRG decreased GM-CSF expression levels in UV-B induced keratinocytes [44] and inhibited the proliferation of GM-CSF induced melanocytes [39] . These findings showed that SKRG had antiproliferative effects on mouse melanocytes and ginsenoside Rh3 and F1 may be effective ingredients that inhibit skin pigmentation stimulated by bFGF following UV-B radiation.…”
Section: Discussionmentioning
confidence: 85%